The Dental Reference Manual : A Daily Guide for Students and Practitioners - Weinstein, Geraldine M.; Zientz, Mitchell T. (Springer International Publishing : Imprint: Springer, 2017)
This book is designed to meet the needs of both dental students and dentists by providing succinct and quickly retrievable answers to common dental questions. Students will find both that it clearly presents the particulars which should be familiar to every dentist and that it enables them to see the "big picture" and contextualize information introduced to them in the future. Practicing dentists, on the other hand, will employ the book as a daily reference to source information on important topics, materials, techniques, and conditions. The book is neither discipline nor specialty specific. The first part is wide ranging and covers the essentials of dental practice while the second part addresses individual specialties and the third is devoted to emergency dental treatment. Whether as a handy resource in the student's backpack or as a readily available tool on the office desk, this reference manual fills an important gap in the dental literature.
Keywords: Dentistry.; Oral surgery.; Maxillofacial surgery.; elektronické knihy; electronic books